Total Anthocyanin Pigments in Thai Herb Vegetable - Theeranat Suwanaruang (Current Topics in Agricultural Sciences Vol. 5, 2021)
One of the most popular North-East of Thai herbs vegetables is Teaw (Cratoxylum formosum). Teaw is an impressive Thai vegetable, mostly grown in the North-East of Thailand., When compared to many species of indigenous Thai plants, the leaf extract was found to have strong antioxidant and antimutagenic properties. The goal of this study was to look at total anthocyanin pigments in Cratoxylum formosum. The means were evaluated in different exaction solutions (water, acetone, ethanol, and methanol) and at different times (0 minutes, 30 minutes and 60 minutes). Chemically weighed samples of 5 g with modification exaction solutions and difference times afterward absorbance samples at 535 nm by spectrophotometer were examined. At 0 minutes, the results in different exaction solutions (water, acetone, ethanol, and methanol) were909.136±75.010, 737.743±734.871, 704.216±2.313and 825.006±14.226 mg/L respectively. At 30 minutes in diversity exaction solutions (water, acetone, ethanol, and methanol), the concentrations were 873.886±8.626,788.503±17.094, 720.98±30.786 and 758.686±37.772 mg/L respectively. At 60 minutes in diverse exaction solutions (water, acetone, ethanol, and methanol), the concentrations were 903.96±75, 764.53±49.984, 735.236±45.783 and 824.38±14.718 mg/L respectively. The highest anthocyanin in Cratoxylum formosumwas exaction with water at 0 minutes (909.136±75.010 mg/L). Cratoxylum formosum is a Thai vegetable that is commonly grown in the north-east of Thailand.